Assessment of Knowledge, Attitude and Practices of Medical Officers in Primary Health Centres Regarding Type 2 Diabetes Mellitus - Appajigol, Jayaprakash S; Somannavar, Manjunath Somappa (Journal of Medicine, 2019)
Background: Health education is an integral part of Type 2 diabetes mellitus (T2DM) management, as it can be prevented and controlled by the implication of appropriate interventions. The aim of the study was to assess the knowledge, attitude, and practice (KAP) of medical officers (MOs) in primary health centres (PHC) regarding T2DM. Materials and methods: The 104 medical officers (MOs) with an experience of £2 years of medical practice were included in the study. A self-completion questionnaire, designed to be completed within 10-15 minutes, was developed to analyse the KAP of the MOs regarding T2DM. Results: Among the 104 MOs, 14 had knowledge about the prevalence of T2DM in India. Among the risk factors, obesity (71), physical inactivity (31), family history (43), and hypertension (15) were identified by the MOs. The microvascular complications, including retinopathy (77), nephropathy (63), and neuropathy (49) were stated by the physicians. However, the physicians were less aware about the macrovascular complications. As few as 23 physicians included HbA1c test as one of the diagnostic methods, 43 physicians included HbA1c to monitor the glycemic levels. More than half (55) of the physicians prescribed appropriate medications for the treatment of T2DM. Conclusions: The MOs had considerable knowledge and attitude about T2DM, however due to lack of facilities at the PHCs, the practice of MOs in the management of T2DM is poor. Education programmes to expand the understanding of the MOs regarding T2DM and initiatives to advance the facilities at PHCs are essential to manage T2DM in India. Keywords: Type 2 Diabetes Mellitus J MEDICINE JUL 2019; 20 (2) : 63-67